Photocatalytic treatment to inhibit the growth of skin cancerous cells - Sharon, Maheshwar (JOURNAL OF ADVANCES IN PHYSICS, 2017)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> A photocatalytic technique has been applied to study the inhibition of growth of cancerous cell . A suspension of semiconducting carbon (band gap 1.2 eV) in methanol (2 mg/ml in methanol) on administering to C6- Glioma (5 x 106 cells) tumor transplanted in Wistar pups and exposing it with visible light (15 Lux) for 30 min. inhibited the growth of cells while exposure of the cells alone either with light or semiconducting carbon did not show any appreciable inhibition. The mechanism responsible to inhibit of the growth of the cell is discussed. It is proposed that some medical practitioners would adopt this technique to cure skin cancer. Walchand Center for Nanotechnology and Bionanotechnology, Walchand College of Arts and Science, Solapur.India <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->